2020
DOI: 10.1186/s12935-020-01241-8
|View full text |Cite
|
Sign up to set email alerts
|

Circ_100565 promotes proliferation, migration and invasion in non-small cell lung cancer through upregulating HMGA2 via sponging miR-506-3p

Abstract: Background: Circular RNAs (circRNAs) play a vital role in the development of various cancers. Circ_100565 was found to be a highly expressed circRNA in non-small cell lung cancer (NSCLC) tissues screened by microarray profiles of circRNAs. However, the role of circ_100565 in NSCLC still remains unknown. Methods: Microarray analysis was used to screen for differentially expressed circRNAs in NSCLC tissues. The expression levels of circ_100565, microRNA-506-3p (miR-506-3p) and high mobility group AT-hook 2 (HMGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…22 Circ_100565 upregulates HMGA2 expression by sponging miR-506-3p to promote migration, invasion, and proliferation. 23 Hsa_circ_0043265 inhibits NSCLC progression by sponging miR-25-3p to promote FOXP2 expression. 24 Here, we used Circinteractome and the intersection of DEMs to identify hsa-miR-532-3p and hsa-miR -942-5p.…”
Section: Discussionmentioning
confidence: 99%
“…22 Circ_100565 upregulates HMGA2 expression by sponging miR-506-3p to promote migration, invasion, and proliferation. 23 Hsa_circ_0043265 inhibits NSCLC progression by sponging miR-25-3p to promote FOXP2 expression. 24 Here, we used Circinteractome and the intersection of DEMs to identify hsa-miR-532-3p and hsa-miR -942-5p.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the proliferation and invasion of HCC are dependent on circMAST1 binding to miR-1299 and inhibiting CTNND1 [23]. Circ_100565 upregulates HMGA2 expression by sponging miR-506-3p to promote migration, invasion, and proliferation [24]. Hsa_circ_0043265 inhibits NSCLC progression by sponging miR-25-3p to promote FOXP2 expression [25].…”
Section: Discussionmentioning
confidence: 99%
“…CircASPH promoted tumor growth in LUAD cells by sponging miR-370 and abrogating miR-370-mediated inhibition of HMGA2 ( 65 ). Li et al also demonstrated that another circRNA, circ_100565 promoted proliferation, migration and invasion of NSCLC by upregulating HMGA2 via miR-506-3p sponging ( 66 ). Moreover, circEPSTI1 aggravated in vitro NSCLC progression by elevating HMGB3 expression via miR-145 sponging ( 67 ).…”
Section: The Role Of Circrnas In Lung Cancermentioning
confidence: 99%